Avaliação da atividade fotocatalítica de nanopartículas de Nb2O5 para degradação de pesticida - Neves Junior, Luiz Ferreira (2014)
From 2010, Brazil ranks as the largest consumer of pesticides in the world, being 99% or more of sprayed pesticides can disseminate to the environment, and consequently reaching the ground and water. A possibility attempt to remedy this contamination is the use of Advanced Oxidation Processes (AOP). These processes consist in formation of highly oxidizing species in a way to mineralize organic molecules. The species can be generated from photoactivation reactions using a semiconductor under ultraviolet-visible radiation. A promising and underexplored semiconductor in catalysis is Nb2O5 which presents notable chemical and physical properties also, niobium is highly available in Brazil and present low cost. This work aimed to evaluate the use of an abundant material in Brazil, niobium, in order to contribute to the resolution of an environmental problem and public health, the water contamination by pesticides. In this way, it tried to draw parallels between the structural, morphological and surface characteristics of the synthesized Nb2O5, and its photocatalytic activity against pesticides. Nb2O5 was synthesized by three different methods, Polymeric Precursors, Hydrothermic and Decomposition. The process was optimized for each method varying different parameters in the employed methodology. The techniques X-ray diffraction (XRD), Scanning Electron Microscopy with Field Emission Gun (SEM-FEG), Zeta Potential, Infrared, Diffuse Reflectance and Raman spectroscopies; were used to characterize the synthesized materials. The photodegradation process under UVC radiation (254 nm) was monitored using UV-spectroscopy in the UV-visible region and its efficiency was evaluated by means of kinetic study. In general, it was found that the polymeric precursors method produces the most efficient Nb2O5 photocatalyst. Thus, this method was used for impregnating the previously synthesized magnetic nanoparticles (magnesium and cobalt ferrites) with Nb2O5, in order to remove the photocatalyst from water and enable to reuse this material. From the obtained results it was observed that the magnetic nanoparticles do not influence the photocatalytic response and may provide the removal and reuse of the photocatalyst.